PHYSICOCHEMICAL AND SENSORY PROPERTIES OF FERMENTED PROSOPIS AFRICANA SEEDS: PHYSICOCHEMICAL AND SENSORY - Sikiru, musbau; R.A , Asiru (INDONESIAN JOURNAL OF HEALTH SCIENCES RESEARCH AND DEVELOPMENT (IJHSRD), 2024)
Background: Fermented Prosopis Africana seeds called Okpehe by the Idoma people of Benue State, Nigeria are a commonly prepared food Condiment added to food so as to improve its aroma and taste  Methods: It was produced in the laboratory using Spontaneous method and preserved for twelve days using different concentration of Clove and Ginger extracts (1.6%, 2.4%, and 3.2%). The aim of the study was to evaluate physicochemical and sensory parameters of fermented Prosopis Africana seeds during preservation.  Results: A total of 100 responses were obtained, out of which 50% of respondents opted for offline purchase of medicines from nearby pharmacies. In conclusion, it was observed that the majority of the population prefers the offline mode of purchase when it comes to the purchase of medicines and other healthcare products, though there are various major advancements in technology and variety of internet services and easy availability of e-medicines.  Conclusion: It can be inferred from this study that the extracts of spices represent an alternative source of natural antimicrobial substances for use in food systems to prevent the growth of food borne microorganisms and extend the shelf-life of the processed food.